INTERNATIONAL NORM AND TRANSNATIONAL CORPORATION: THE CONTRIBUTION OF L'ORÉAL TO ERADICATE CHILD LABOR MICA MINING IN INDIA - Zain Maulana; Ika Hidayani Harahap (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2021)
This article explores how L’Oréal respond to to the issue of illegal activities and child labour in their mica supply chain from India. It emphasizes that despite economic interests are always embedded in transnational corporation’s, L’Oréal responses to the issue of illegal and child labour mica mining suggest that the action of the company is influenced by international norm such as the UN Guiding Principles on Business and Human Rights. The Guiding Principles has influenced the construction of the L’Oréal identity and behaviour in their business activities. The company has used their business code of conduct in related to human rights in justifying their responses to deal with the illegal and child labour in its mica supply chain from India. It has been emphasized that mica supply from India should comply with globally recognized workplace employment, occupational health and safety, and environmental standards that include prohibitions on the use of child labour.